Raman spectroscopy for unlabelled detection and quantification of drugs in tissue - Woodhouse, Nathan (2023)
Raman spectroscopy is an optical analysis technique for chemical analysis of samples. Inthis thesis, we have assessed its applicability in quantitative detection of drugs within animal tissue. This involved the design, construction, and optimisation of a Raman microscope for this application, considering the specific requirements of the samples. A Raman microscope was designed to efficiently measure Raman spectra from thin (16 μm) tissue sections with >1 cm field-of-view. Two of these were built, one with a 671 nm and one with a 785 nm wavelength excitation laser, to assess the relative benefits of each for drug detection specifically in the Raman silent region of the Raman spectrum (~ 1800 – 2800 cm-1), in both low and highly autofluorescing tissue. These instruments, and the acquisition parameters used, were optimised to maximise Raman throughput while minimising the effects of noise on the measurements from autofluorescence. Control tissue cryosections with drug solution pipetted on top was used as a feasibility test for qualitative detection of drugs in tissue. A model for prediction of the spectra and required measurement times for detection of different drug/tissue combinations at different concentrations was developed. The most promising drugs from this study were then used to generate mimetic tissue models, homogenous mixtures of drug and tissue with known mass ratios, to assess the quantifiability of Raman spectroscopy in drug detection in tissue. Detection limits as low as 18 μg/g were calculated for ponatinib in rat brain mimetic tissue models with 2-hour measurement times, and 34 μg/g for the ponatinib in rat liver mimetic tissue models.